오렌지색계 중형 심비디움 ‘Orange Bowl’ 육성 - 김미선(Mi-Seon Kim); 이혜경(Hye-Kyung Rhee); 박상근(Sang-Gun Park); 정향영(Hyang-Young Jung); 최성열(Sung-Yul Choi); 임진희(Jin-Hee Lim) (Weon'ye gwahag gi'sulji, 2011)
Cymbidium 'Orange Bowl' (Lucky Rainbow 'Randevous' ${×}$ 'Eastern Star') was developed from a cross between hybrids at the National Institute of Horticultural & Herbal Science, Rural Development Administration in 2006. A cross was made between the pink colored flower C. Lucky Rainbow 'Randevous' as maternal line and pure yellow colored flower, C. 'Eastern Star' as paternal line in 1995. The seed germination, cultivation, selection, and characteristic trials were conducted from 1996 to 2006. The line was named as Wongyo F1-18 and phenotype was characterized in 2006 as a new 'Orange Bowl'. The 'Orange Bowl' has having light yellow basal color (RHS, YO21D) and orange line (RHS, OR30B) on both of sepal and petal with red lip (RHS, OR30B). 'Orange Bowl' has about 10.9 flowers per flower stalk and flower size of 7.4 cm. General appearance of the petals and sepals is slightly incurved shape. The plant size is intermediate having erect peduncle. Blooming is started from the late of January (mid winter) under optimal culture condition. Leaf attitude and twisting is half- erect and very weak respectively. This hybrid has attractive floral arrangement, long flower stalk (71.8 cm) and vigorous growth. We expect that 'Orange bowl' has a great potential for exporting to Chinese market. 농촌진흥청 원예특작과학원에서는 2006년에 분홍색과 황색 조합형의 수출용 중 대형품종을 육성할 목적으로 1995년에 분홍색계열의 Lucky Rainbow 'Randevous' 와 황색계 중 형종 'Eastern Star' 품종을 교배하여 오렌지색톤의 심비디움 '오렌지볼'(Cymbidium 'Orange Bowl') 신품종을 개발하였다. 1996년부터 2006년까지 종자기내파종, 온실양성, 선발 그리고 특성검정으로 균일성, 안정성, 화색, 화수, 엽형등이 우수하여 2006년 12월 농작물 직무육성 심의회를 거쳐 'Orange Bowl'로 명명하였다. 'Orange Bowl' 품종은 화색이 노랑색 꽃잎 바탕색(RHS, YO21D)에 주황색의 굵은선(OR30B)이 있어 두가지 화색으로 독특하며, 1개 꽃대에 10.9개의 소화가 착생하며 화폭이 약 7.4cm로 크다. 꽃모양은 꽃받침과 꽃잎이 안쪽으로 약간 오므라드는 둥근 모양이고 꽃대는 반직립성이며 식물체 크기는 중형이다. 꽃은 보통재배시 한겨울인 1월 하순경부터 개화하는 중 생종이며 잎 형태는 꼬임이 적은 반직립성이고 꽃대의 길이는 71.8cm로 강건하여 수출용 재배에 적합하다.